Multiculturalism in question: thoughts around the afro colombian case (2013)
This paper seeks to address the reasons which have generated the lost of visibility and political representation of Afro-Colombians as an ethnic group, in a country which sees itself as being multicultural. Here we offer a tentative answer that questions the Colombian multiculturalism by the articulation of three explanatory elements: 1) the Afro-Colombian movement's fragility as a political actor; 2) the problematic essentialist definition of the afro-Colombian ethnic identity and its political use and; 3) the limits of the multiculturalism model when confronted with the complex Afro-Colombian case. We conclude with a criticism of the Colombian multiculturalism model and a consideration about what its present challenge is.